When Learners Read in Two Languages: Understanding Chinese-English Bilingual Readers Through Miscue Analysis - Blair, Heather; Filipek, Jacqueline; Fu, Hongliang; Lin, Xiaobing; Sun, Miao (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2022)
The number of Chinese-speaking students in Canadian schools is increasing dramatically. This article discusses a study in which we explored reading processes in Chinese and English through examining children’s reading in both languages. Based in a socio-psycholinguistic framework (K. Goodman, Wang, Iventosch, & Y. Goodman,2012; Kabuto, 2017) and through using miscue analysis, we examined how children apply their knowledge of language to Mandarin and English reading. This qualitative research included interviews with four Chinese-English bilingual children between grades 3 and 5 in an urban center as well as the analysis of their reading performance in both languages. From a comparative perspective, we discuss some of the similarities and differences between these two different orthographic language systems by offering syntactic comparisons of the two languages through psycholinguistic language cueing systems. We believe that knowing about how Chinese and English readers construct meaning in both languages will help English as an Additional Language (EAL) teachers, in fact all classroom teachers, to teach reading to bilingual and biliterate children.